The Application of Jigsaw Type of Cooperative Learning Model in Learning Mathematics at SMP SWASTA PEMBDA 2 Gunung Sitoli 2018/2019 Academic Year - Telaumbanua, Yonata (Al'Adzkiya Journal, 2022)
Jigsaw cooperative learning model is a learning model that shapes students' knowledge by means of discussion. However, what distinguishes this model from other models is that there is a group of experts whose knowledge is obtained from the results of discussions in one group about one material that is different from other groups. After this group of experts gets enough knowledge, they will form a new group where the members come from different expert groups.The objectives of the study: (1) describing the quality of the mathematics learning process through the application of the jigsaw type cooperative learning model at the Pembda 2 Gunungsitoli Private Junior High School. (2) Describing student learning outcomes in mathematics subjects through the application of the jigsaw type cooperative learning model at the Pembda 2 Gunungsitoli Private Junior High School. (3) Significantly proving the quality of the mathematics learning process is good by applying the jigsaw type cooperative learning model. (4) Significantly proving that the average mathematics learning outcomes are good by using the jigsaw type of cooperative learning model.This research was carried out at the SMP Swasta Pembda 2 Gunungsitoli with the research subjects was class VIII students of the 2018/2019 academic year in even semester with a total of 34 people, consisting of 18 boys and 16 girls. The research conducted was classroom action research (CAR) which consisted of two cycles with the main material being Statistics. The material for the first cycle is the Mean, Median and Mode, while the material for the second cycle is the Range and Quartile